2010
DOI: 10.1017/s1041610209991554
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant use and depressive symptomatology among older people from the Australian Longitudinal Study of Ageing

Abstract: Use of antidepressants increased, while depressive symptoms remained stable, in the ALSA over a 12-year period. Use of antidepressants was low for people with depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 38 publications
6
24
2
Order By: Relevance
“…Consistent with past research, 8, 9, 11 medical illnesses and somatic complaints were associated with AD use. It might be the case that associations between a physical complaints or illnesses and AD use are explained by access to primary care physicians by individuals with chronic medical conditions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with past research, 8, 9, 11 medical illnesses and somatic complaints were associated with AD use. It might be the case that associations between a physical complaints or illnesses and AD use are explained by access to primary care physicians by individuals with chronic medical conditions.…”
Section: Discussionsupporting
confidence: 86%
“…6 There is some evidence that this potential AD use without an indicated mental disorder diagnosis may be more pronounced in some population subgroups, including females, 8-11 older adults, 8, 10 whites 2 and individuals with physical health problems. 8, 9, 11 Furthermore, some of the individuals who continue to use antidepressants on a long-term basis might have met the criteria for a mental disorder in remote past. While long-term maintenance AD treatment may be indicated in some of these individuals, 12 long-term use of these medications is not always indicated.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized clinical trials performed on depressed older adults samples have demonstrated moderate to large effect sizes for selective serotonin re-uptake inhibitors, tricyclic antidepressants and monoamine oxidase inhibitors [21]. Nevertheless, only a small proportion of older adults with depression (around 20%) receive adequate treatment [22, 23]. Lack of treatment among older adults may reflect, in part, the difficulty of detecting depression in older adults, due to age-specific presentation of disease: compared with young adults, older patients tend to present less emotional symptoms of depression, such as sadness, worthlessness/guilt, worry, and fear, and are less accurate at identifying depressive symptoms overall [24].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of major depression is over 14% among homecare patients (1) with no significant racial differences (2). Over the past decade, rates of antidepressant use in geriatric patients have increased substantially (3); with recently available national data on homecare patients showing that 1/3 were prescribed an antidepressant (4, 5). These data will also be used in this study to compare antidepressant use in whites and blacks.…”
Section: Introductionmentioning
confidence: 99%